1992
DOI: 10.1073/pnas.89.21.10169
|View full text |Cite
|
Sign up to set email alerts
|

Ser-752-->Pro mutation in the cytoplasmic domain of integrin beta 3 subunit and defective activation of platelet integrin alpha IIb beta 3 (glycoprotein IIb-IIIa) in a variant of Glanzmann thrombasthenia.

Abstract: Medical SciencesSer-752 -> Pro mutation in the cytoplasmic domain of integrin .83 subunit and defective activation of platelet integrin aIlbP3 (glycoprotein lib-Illa) in a variant of Glanzmann thrombasthenia (molcular genetlcs/flbnnogen receptor/Arg-Gly-Asp/poyerase chan reacdon) YI-PING CHEN*, ISABELLE DJAFFAR*, DOMINIQUE PIDARDt, BEAT (8,9), as well as for aLI32 (10). At least in the case of amb43 activation, modulation of affinity for its ligands is coordinated with conformational changes of the integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
164
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(169 citation statements)
references
References 41 publications
4
164
1
Order By: Relevance
“…It is of interest to compare our data on the clamped receptor with observations on the platelets of a patient with Glanzmann thrombasthenia who had intact ␣IIb␤3 ectodomains but whose receptors were insensitive to inside-out signaling as a result of a mutation in the ␤3 cytoplasmic domain (26,36). The patient's receptors were able to support platelet adhesion to immobilized fibrinogen but not soluble fibrinogen binding in response to agonist stimulation.…”
Section: Discussionmentioning
confidence: 93%
“…It is of interest to compare our data on the clamped receptor with observations on the platelets of a patient with Glanzmann thrombasthenia who had intact ␣IIb␤3 ectodomains but whose receptors were insensitive to inside-out signaling as a result of a mutation in the ␤3 cytoplasmic domain (26,36). The patient's receptors were able to support platelet adhesion to immobilized fibrinogen but not soluble fibrinogen binding in response to agonist stimulation.…”
Section: Discussionmentioning
confidence: 93%
“…The point mutation Ser7523 Pro in the ␤ 3 cytoplasmic tail was associated with an apparent ␣ IIb ␤ 3 activation defect in a patient with Glanzmann's thrombasthenia. 10 Prolonged inhibition of Ser/Thr phosphatases by calyculin A increased the phosphorylation of Thr753, which was accompanied by a decrease in platelet adhesion and spreading on surface-coated fibrinogen. 42 In an attempt to compete with the native integrin subunit for regulatory signals, peptides that mimic different, but partially overlapping, domains of the ␤ 3 subunit were designed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with Glanzmann's thrombasthenia, a severe bleeding disorder, have platelets that either lack ␣ IIb ␤ 3 (type I) or contain a defective ␣ IIb ␤ 3 that is unable to expose ligand binding sites (type III). 10 The Ser7523 Pro mutation in the ␤ 3 subunit of type III patients is of particular interest because it results in the loss of ligand binding. 11 Platelet agonists trigger inside-out signaling to ␣ IIb ␤ 3 via protein tyrosine kinases (PTKs) as herbimycin A, tyrphostin A47, and geldanamycin inhibit ligand binding.…”
mentioning
confidence: 99%
“…2, A and C). Previous studies have shown that a proline substitution mutation at Ser 752 , which is found in a variant of Glanzmann thrombasthenia, suppresses ␣IIb␤3 integrin activation (49,50). The S752P point mutation does not impair talin-H binding (28).…”
Section: Discussionmentioning
confidence: 99%